ANALISIS DATA BLR DAN EAR DALAM MENGKAJI FENOMENA MJO DAN KETERKAITANNYA DENGAN CURAH HUJAN DI ATAS KOTOTABANG DAN SEKITARNYA - Eddy Hermawan; Arief Suryantoro; Mega Puspawardhany; Tri Wahyu Hadi; Udjianna S. Pasaribu; Findy Renggono (Jurnal Sains Dirgantara, 2006)
This paper is mainly concerned to the analysis of Madden Julian Oscillation (MJO) phenomena crossing over Kototabang, West Sumatere and surrounding areas using Boundary Layer Radar (BLR) and Equatorial Atmosphere Radar (EAR) data taken from September to December 2001 as cintinuing studied by Indriaty (2005). We are interested to continue, especially on the effect of MJO phenomena on the daily rainfall intensity distribution over Kototabang and surrounding area. We divided data into two steps analysis. First is the vertical profile analysi using BLR and EAR data, and the second step is surface analysis using RAINFALL INTENSITY DATA FROM TAKEN FROM THREE METEOROLOGICAL STATIONS IN wEST sUMATERA. tHEY ARE bADAN mETEOROLOGI DAN gEOFISIKA (bmg) Sicicin station (0.6˚LS; 100.22˚BT), BMG-Padangpanjang station (0.5˚LS; 100.41˚BT) and Statsiun Pengamat Dirgantara (SPD) LAPAN Kototabang (0.2˚LS; 100.32˚BT). The vertical profile of zonal-vertical wind vector of EAR data analysis shows that the pre-dominant wind mived to east direction, especially in surface layer, while in the upper troposhere the pre-dominant wind moved to the opposite direction, especially from September to December 2001. This result looks a siminar with the schematic theory of the MJO cross section along equator that described by Matthews (2000). A simiinar result is also shown by the BLR data analysis. Both EAR and BLR data are siminar each other. Since the MJO phenomena is expected passing over Kototabang around mid of November to mid of December 2001, we are interested to analysis the as already mentioned above using the global wavelet spectrum technique. The result shows that their pre-dominant peak ascillation is about 48 days. This result is consistent with the Outgoing Longwave Radiation (OLR) anomaly taken from infra-red sensor of satellite that already been done by Matthews (2000). While, the cross correlation function (CCF) analysis between zonal wind and rainfall data shows unsignificant (very small) value. We suspect that the surface rainfall intensity over Kototabang and surrounding area is not mainly dominanted by MJO phenomena.